2014
DOI: 10.1016/j.bbmt.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection in Patients Who Underwent Allogeneic Hematopoietic Stem Cell Transplantation in Portugal: A Five-Year Retrospective Review

Abstract: Cytomegalovirus (CMV) infection is 1 of the leading causes of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (aHSCT), mainly within the first 100 days after transplantation. We aimed to characterize CMV infection in a cohort of 305 patients with different malignancies undergoing aHSCT at the Portuguese Institute of Oncology of Porto between January 2008 and December 2012. In total, 184 patients (60.3%) developed CMV infection, mainly viral reactivations rather than primary inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 58 publications
5
46
2
3
Order By: Relevance
“…In an analysis of a Portuguese cohort that comprised 85.81% CMV-seropositive recipients and 73.27% CMV-seropositive donors, Sousa et al [14] observed that 60.3% of patients developed CMV infection after allo-HSCT. In our study, 92.68% of recipients and 85.37% of donors were CMV-seropositive, but the incidence of CMV reactivation was only 39.02%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of a Portuguese cohort that comprised 85.81% CMV-seropositive recipients and 73.27% CMV-seropositive donors, Sousa et al [14] observed that 60.3% of patients developed CMV infection after allo-HSCT. In our study, 92.68% of recipients and 85.37% of donors were CMV-seropositive, but the incidence of CMV reactivation was only 39.02%.…”
Section: Discussionmentioning
confidence: 99%
“…Sousa et al [14] found that CMV infection was associated with inferior median post-transplantation survival in allo-HSCT recipients. However, the data from our cohort did not show a statistically significant difference in OS between patients with and without CMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Allojenik HKHT alıcıla-rında CMV majör virüslerden biridir. CMV seropozitif alıcıların %45-65'inde reaktive olur ve bu hastaların %20-30'unda CMV hastalığı gelişir [1][2][3] . CMV infeksiyonu tipik olarak, HKHT'den sonraki ilk 100 gün içinde görülür ve başlıca pnömoni ve gastrointestinal hastalığa yol açar.…”
Section: Discussionunclassified
“…İlk infeksiyon sonrasında virüs lenfositlerde, monositlerde ve dendritik hücrelerde latent kalır. Allojenik HKHT alıcılarında CMV infeksiyonu asemptomatik infeksiyondan pnömoni, hepatit, gastroenterit, retinit ve ensefalite değişen çeşitli hastalıklarla ilişkilidir [1,3,4] . Yine herpesvirüs ailesinin üyesi olan Epstein-Barr virüs (EBV) popülasyonun %90'dan fazlasını infekte eden yaygın bir virüstür.…”
Section: Introductionunclassified
“…CMV infection in HSCT patients manifests as enterocolitis, pneumonia, hepatitis or as retinitis and bone marrow suppression (Russell et al, 2011). Although less frequently, late CMV reactivation (>100 days posttransplant) can occur (Cervera et al, 2007;Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%